1999
DOI: 10.1038/sj.bjp.0702448
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the behaviour of selected CCKB/gastrin receptor antagonists in radioligand binding assays performed in mouse and rat cerebral cortex

Abstract: James Black Foundation, 68 Half Moon Lane, Dulwich, London SE24 9JE, England 1 The previously described complex behaviour of the CCK B /gastrin receptor antagonist, L-365,260, in radioligand binding assays could be explained by a variable population of two binding sites. We have investigated whether other CCK B /gastrin receptor ligands (PD134,308, PD140,376, YM022 and JB93182) can distinguish between these sites. 2 In the mouse cortex assay, Hill slopes were not dierent from unity and the ligand pK I values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 24 publications
5
27
2
Order By: Relevance
“…The competitors all behaved simply in the gallbladder assay with Hill slopes not significantly different from unity. The corresponding p K I value for 2‐NAP was indistinguishable from previously reported affinity estimates obtained in a guinea‐pig pancreas ([ 125 I]‐BH‐CCK‐8S) binding assay (p K I =5.3; Harper et al ., 1999) and gallbladder smooth muscle functional bioassays (human pA 2 =5.9, guinea‐pig pA 2 =6.4; Hull et al ., 1993). The values obtained for L‐364,718 and SR27897, although still consistent with selective CCK 1 receptor binding, were higher than those previously reported at human CCK 1 receptors (SR27897 p K I =8.7 at the cloned receptor, Gigoux et al ., 1999; L‐364,718 p K I =9.2 in human gallbladder membranes; Xiao et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The competitors all behaved simply in the gallbladder assay with Hill slopes not significantly different from unity. The corresponding p K I value for 2‐NAP was indistinguishable from previously reported affinity estimates obtained in a guinea‐pig pancreas ([ 125 I]‐BH‐CCK‐8S) binding assay (p K I =5.3; Harper et al ., 1999) and gallbladder smooth muscle functional bioassays (human pA 2 =5.9, guinea‐pig pA 2 =6.4; Hull et al ., 1993). The values obtained for L‐364,718 and SR27897, although still consistent with selective CCK 1 receptor binding, were higher than those previously reported at human CCK 1 receptors (SR27897 p K I =8.7 at the cloned receptor, Gigoux et al ., 1999; L‐364,718 p K I =9.2 in human gallbladder membranes; Xiao et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The values obtained for L‐364,718 and SR27897, although still consistent with selective CCK 1 receptor binding, were higher than those previously reported at human CCK 1 receptors (SR27897 p K I =8.7 at the cloned receptor, Gigoux et al ., 1999; L‐364,718 p K I =9.2 in human gallbladder membranes; Xiao et al ., 1999). The lower affinity values estimated for the CCK 2 ‐receptor selective ligands were also consistent with their interaction at the CCK 1 ‐receptor subtype in animal tissue (p K I for YM220=8.1, PD‐134,308=6.1, JB93182=5.3; Harper et al ., 1999), which demonstrated that the selectivity of these compounds was maintained in human tissue. In contrast, in the human colon assay the competition curves for SR27897, 2‐NAP, YM220 and PD‐134,308 were all significantly flat and better described by the two‐site rather than the one‐site model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were then fed by the capillary feeding assay method for 2-3 days with 1, 3, and 5 mM of the octopamine antagonists phentolamine (Dudai 1982), Sigma-Aldrich) or epinastine (Stevenson et al 2005;Unoki et al 2005) or with 1 mM CCK antagonist (SR27897, Sigma-Aldrich) (Harper et al 1999). Each fly was transferred to a transparent plastic cylindrical vial (9 3 2 cm) (height 3 diameter), containing 1% agarose (5 cm high) to provide moisture and humidity for the flies, and the opening of the vial was covered with paraffin film.…”
Section: Antagonist Assaysmentioning
confidence: 99%
“…18 Competition radioligand binding studies with diverse CCK 2 receptor antagonists have provided evidence for the existence of two binding sites, or binding states, for this receptor subtype in gastric glands and cortex of some animal species. [68][69][70] Furthermore, the distinct behavioral responses elicited by the CCK 2 selective agonists BC 197 (anxiogenic) and CB 264 (nonanxiogenic and increases memory and attention) have been also related with the existence of two different binding states of these receptors in the brain. 71,72 …”
Section: B Cck 2 Receptorsmentioning
confidence: 97%